Efecto del biofungicida SIP 41034 sobre Botrytis cinerea en vid - D'innocenzo, Sandra Haydeé; Arias, Maria Fernanda; Longone, Maria Valeria; Escoriaza, Maria Georgina; Nasiff, E. A.; Markan, E. D. (Asociación Argentina de Fitopatología (AAF), 2025)
Póster y resumen